2017
DOI: 10.1111/cbdd.13131
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the agonist action at free fatty acid receptor 1 (FFA1R or GPR40)

Abstract: G-protein-coupled receptor 40 (GPR40) was recently identified as an interesting target for treatment of type 2 diabetes. The high level of expression in pancreatic beta cells and the dependence of glucose on stimulating the secretion of insulin led to great excitement in this field. The identification of this target was followed by the development of a series of agonists with great potential for the treatment of diabetes. All known agonists have the presence of a pharmacophoric carboxylic acid group in their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, such a tactic may sacrifice metabolic stability of the ligand; therefore pursuing such van der Waals interactions was not a practical option in this case. Alternatively, implementation of a polar functionality outside the binding pocket is a viable strategy, and a number of successful examples have been reported in the literature. , The X-ray cocrystal structure of our first generation inhibitor suggested a substituent at the β-position of the propanoyl moiety would project toward the outside the pocket (Figure ), so we introduced substituents bearing a functional group at the terminus and examined their effects on metabolic stability and other pharmacokinetic parameters.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, such a tactic may sacrifice metabolic stability of the ligand; therefore pursuing such van der Waals interactions was not a practical option in this case. Alternatively, implementation of a polar functionality outside the binding pocket is a viable strategy, and a number of successful examples have been reported in the literature. , The X-ray cocrystal structure of our first generation inhibitor suggested a substituent at the β-position of the propanoyl moiety would project toward the outside the pocket (Figure ), so we introduced substituents bearing a functional group at the terminus and examined their effects on metabolic stability and other pharmacokinetic parameters.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Except carbon chain length dependency, the structure–activity relationships of fatty acid properties such as degree of unsaturation, position or cis – trans isomerism of double bond(s) have not been established. Although various GPR40 agonists has been developed, none of them possess the structures found in the present study. The present study revealed two distinct structures related to potent activation of GPR40‐mediated CCK secretion in enteroendocrine cells.…”
Section: Discussionmentioning
confidence: 91%
“…Chemically they resemble those from the '575 document closely, with most of the structure -in many cases, including the characteristic terminal carboxycyclopropyl group -preserved. (All known GPR40 agonists contain a pharmacophoric carboxylic acid group in their structure, allowing several polar interactions at the binding site of this receptor [47].) While diabetes clearly is the primary development target for free fatty acid receptor agonists, they might be useful in other therapeutic fields; for antagonists, suppression of inflammatory responses in periodontal diseases could be an example [48].…”
Section: Wo/2018/086530mentioning
confidence: 99%